Communication system in Turkey: the effect on economic development - Nor Hazila Mohd Zain; Mohd Safar Hasim; Mohamad Abdul Hamid; Mohd Rizal Palil (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
Telecommunication in many countries has been playing a significant role in developing the economy. The positive relationship between the growth of telecommunication and the economy has evidenced that one of the main factors in developing the economy is by focusing more on the communication system in a country. History has shown that during the World War I and II, effective communications has evidenced that it can lead to victory. Communication is defined as a system that senders have possibility to send message to receiver in general meaning and it has long been recognized that communications might have a central role in development. This paper attempts to discuss the role of communication system in Turkey. The discussions are limited to types of communication in Turkey including newspaper and magazines, internet, postal services and fixed-line telephone and mobile phone. The growth of telecommunication in Turkey has increased the per capita income from to USD13,737 in 2013 compared to USD13,609 and USD12,671 in 2012 and 2011 respectively. Moreover, the Turkish economy has also developing in a better shape compared to the last 10 years before communications such as Internet and mail services taking place. These evidences have proven that telecommunications technology significantly affect economic growth in a country especially in Turkey. Furthermore, huge investment on communication systems nowadays is imperative as the return on investment is worthwhile by virtue of increasing the GDP and boosting the economy.